EFEKTIVITAS MEDIASI DALAM PENYELESAIAN SENGKETA ANTARA KONSUMEN LISTRIK DENGAN PELAKU USAHA (PLN) PADA BADAN PENYELESAIAN SENGKETA KONSUMEN PROVINSI RIAU - Rifqianda, Rentri; Ismi, Hayatul; Dasrol, Dasrol (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Hukum, 2019)
The State of Indonesia is a State of Law. These provisions mean that the Indonesian state is a democratic rule of law based on the Pancasila and the 1945 Constitution, upholds human rights, and guarantees all citizens at the same time their positions in the law and government are goodThe government makes policies and programs in the supply of electricity controlled by the state in its implementation carried out by PT. PLN (Persero) as a state-owned enterprise. The implementation of electricity supply business was formed based on Law number 30 of 2009 concerning electricity. However, in its implementation a lot of law violations occur. Along with the development of electricity development accompanied by the emergence of a variety of problems surrounding the electricity sector in Indonesia. One of them is a business actor (PLN) that does not carry out its obligations to consumers and vice versa. To support government policies and programs in resolving consumer disputes, the government has established a non-litigation judicial body based on the Consumer Protection Act, namely the Consumer Dispute Settlement Agency (BPSK) specifically handling consumer problems with business actors through channels outside the Court.The purpose of writing this thesis, namely; First, to find out the effectiveness of mediation in the resolution of disputes between electricity consumers and business actors (pln) at the Riau provincial consumer dispute resolution body, Second; know the factors that become obstacles in the effectiveness of mediation in the resolution of disputes between electricity consumers and business actors (pln) at the riau provincial consumer dispute resolution body, Third find out what efforts are being made to overcome obstacles in mediation in dispute resolution between electricity consumers and business actors (pln) at the Riau Province Consumer Dispute Resolution AgencyFrom the results of the research based on three problem formulations it can be concluded, First, mediation in dispute resolution between consumers and business actors (PLN) at the Riau provincial consumer dispute resolution body is not yet effective. the role of the Riau provincial consumer dispute resolution body should be used as a forum for dispute resolution in order to provide legal protection to both parties. secondly, the mediation process in resolving disputes between electricity consumers and business actors (pln) at the Riau provincial consumer dispute resolution body still has obstacles in terms of financial, operational and existence of the consumer dispute resolution agency itself. And must be able to be used as a container in providing legal certainty to both parties. third hope that the consumer dispute resolution body can work optimally and consumers and business actors obtain legal certainty in dispute resolution, it must be separated between dispute resolution through litigation (court) and dispute resolution through the consumer dispute resolution agencyKeywords: Effectiveness-Consumer Dispute Resolution Agency-Mediation-PLN